2021
DOI: 10.7554/elife.67024
|View full text |Cite
|
Sign up to set email alerts
|

Latent gammaherpesvirus exacerbates arthritis through modification of age-associated B cells

Abstract: Epstein-Barr virus (EBV) infection is associated with rheumatoid arthritis (RA) in adults, though the nature of the relationship remains unknown. Herein, we examine the contribution of viral infection to the severity of arthritis in mice. We provide the first evidence that latent gammaherpesvirus infection enhances clinical arthritis, modeling EBV's role in RA. Mice latently infected with a murine analog of EBV, gammaherpesvirus 68 (gHV68), develop more severe collagen-induced arthritis and a Th1-skewed immune… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 62 publications
(138 reference statements)
3
15
0
Order By: Relevance
“…In the γHV68 EAE model, we also observe greater CD8 + T cell infiltration of the CNS, and particularly the brain, of latently infected mice, in addition to Th1-skewing, macrophage/microglia and DC activation, and reduced Treg proportions in the CNS and periphery 61, 73 . Similar Th1-skewing and CD8 + T cell involvement was observed in latent γHV68-infected mice induced with rheumatoid arthritis 74 , suggesting a common role for gammaherpesviruses in the exacerbation of and predisposition for autoimmunity. Ingelfinger et al recently identified increased CD25 expression on transitional helper T cells as a defining phenotype of MS-derived PBMC in a monozygotic twin study, which the authors posit could be preferentially responsive to an environmental immune challenge such as EBV infection 75 .…”
Section: Discussionsupporting
confidence: 55%
“…In the γHV68 EAE model, we also observe greater CD8 + T cell infiltration of the CNS, and particularly the brain, of latently infected mice, in addition to Th1-skewing, macrophage/microglia and DC activation, and reduced Treg proportions in the CNS and periphery 61, 73 . Similar Th1-skewing and CD8 + T cell involvement was observed in latent γHV68-infected mice induced with rheumatoid arthritis 74 , suggesting a common role for gammaherpesviruses in the exacerbation of and predisposition for autoimmunity. Ingelfinger et al recently identified increased CD25 expression on transitional helper T cells as a defining phenotype of MS-derived PBMC in a monozygotic twin study, which the authors posit could be preferentially responsive to an environmental immune challenge such as EBV infection 75 .…”
Section: Discussionsupporting
confidence: 55%
“…We observed that ABCs contribute to EAE in a protective manner, as knocking them out results in an exacerbation of disease, while in a model of SLE ABCs appear to be contributing pathogenically (12). We have previously found that knocking out ABCs has no impact on the clinical course of collagen-induced arthritis, though mice without ABCs do not show the gHV68-exacerbation of arthritis that is observed in control mice (45). The finding that ABCs are required for the gHV68 exacerbation of both CIA and EAE brings up the question of whether ABCs are a conserved mechanism by which gammaherpesvirus contributes to both arthritis and MS.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, this group reports that mice with B cells deficient in T-bet can generate CD11c + CD11b + ABC-like B cells in a model of lupus [ 43 ]. Alternatively, other groups, including our own, have shown a marked loss in CD11c-expressing ABCs in mice with T-bet-deficient B cells [ 41 , 44 ]. This indicates that CD11c expression is not necessarily a downstream effect of T-bet in all circumstances, but rather CD11c expression increases as a result of appropriate stimuli.…”
Section: Discussionmentioning
confidence: 96%
“…HCV-induced ABC-like cells produce rheumatoid factor-type autoantibodies [ 53 ]. Additionally, we have recently demonstrated that T-bet + B cells are required for ɣHV68 exacerbation of arthritis and EAE [ 36 , 44 ]. It is well established that the ABC population expands with age [ 1 , 34 , 35 ], but how this increased abundance impacts viral infection and autoimmunity remains understudied.…”
Section: Discussionmentioning
confidence: 99%